1980
DOI: 10.2307/1166011
|View full text |Cite
|
Sign up to set email alerts
|

Experience and the Development of Intelligence in Young Children at Home and in Day Care

Abstract: This study examined the relationship between the antecedent everyday experiences of middle-class children in middle-class day-care centers and their intellectual development assessed by the Binet and tests of Spatial Abilities and Receptive Language at age 3. As in the previous study of children in home care, certain types of experiences were hypothesized in advance to be intellectually valuable in that they seemed to provide the clearest opportunities for the child to learn the skills required for successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
2

Year Published

1986
1986
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(60 citation statements)
references
References 33 publications
3
55
2
Order By: Relevance
“…Surely this older group had even more exposure to video (Anderson & Lorch, 1983;Carew, 1980), yet they apparently recognized the connection between the video presentation and reality. The answer may be that the 2%-year-olds had also had more general symbolic experience, that is, more exposure to a wide variety of symbols and symbolic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Surely this older group had even more exposure to video (Anderson & Lorch, 1983;Carew, 1980), yet they apparently recognized the connection between the video presentation and reality. The answer may be that the 2%-year-olds had also had more general symbolic experience, that is, more exposure to a wide variety of symbols and symbolic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Home and the child care physical environments together lead to better child development (including language development) than only the home or the child care physical environments (Clarke-Stewart, 1984;Phillips & Howes, 1987). Some other studies, however, have reported controversial results on what role is played by the physical play environment (Ackerman-Ross and Khanna, 1989;Carew, 1980;Cazden, 1966). Ackerman-Ross and Khanna (1989) have not found that language performance is related to the availability of materials.…”
Section: Physical Environment and Language Developmentmentioning
confidence: 98%
“…So, for example, complex associations have been observed at specific points and across specific time spans in development as well as across specific domains of development (e.g., Bornstein 1989a, Lewis & Gregory 1987, Vibbert & Bornstein 1989, Wachs & Gruen 1982. On the basis of this research (e.g., Belsky et al 1980, Bornstein 1985, Carew 1980, Clarke-Stewart 1973, Clarke-Stewart & Hevey 1981, Slade 1987a, Wachs & Chan 1986, Zukow 1986), we hypothesized that parent-toddler interactions and toddler cognitive competencies would covary in specific and differentiated ways, such that parents' social interactions would relate to toddlers' play (rather than to language) competencies whereas parents' didactic interactions would relate to toddlers' language (rather than to play) capacities. Some research has pointed to contrasting patterns of verbal and non-verbal interaction styles in mothers and fathers (e.g., Clarke-Stewart 1978, Crawley & Sherrod 1984, Landerholm & Scriven 1981, McLaughlin, White, McDevitt & Raskin 1983, Parke 1981, Power & Parke 1983, Rondal 1980, Teti, Bond & Gibbs 1988).…”
Section: Introductionmentioning
confidence: 71%
“…Parental social interactions with children include the visual, verbal and physical behaviours used in engaging children in interpersonal exchanges, like play, mutual visual regard and reciprocal vocalizing (e.g., Beckwith 1972, Bornstein & Tamis-LeMonda 1989, Fiese 1990, Hardy-Brown, Plomin & DeFries 1981, Junefelt 1990, Matas, Arend & Sroufe 1978, Slade 1987a, 1987b, Sorce & Emde 1981. Parental didactic interactions consist of strategies used in stimulating children to engage and understand their environment, like involving play with toys, encouraging joint attention to surroundings, and describing and demonstrating (e.g., Belsky, Goode & Most 1980, Bornstein 1985, Bradley, Caldwell & Elardo 1979, Carew 1980, Clarke-Stewart 1973, Olson, Bayles & Bates 1986, Smith et al 1988, Wachs & Chan 1986. By the beginning of the second year, toddlers understand and differentiate the animate and inanimate worlds (Frye 1981, Gelman & Spelke 1981, Golinkoff 1983, Piaget 1981, and research shows that parental interactions with infants and toddlers increasingly distinguish these social and didactic orientations (e.g., Belsky, Gilstrap & Rovine 1984, Bornstein & TamisLeMonda 1990, Brown 1977, Penman, Cross, Milgrom-Friedman & Meares 1983.…”
Section: Introductionmentioning
confidence: 99%